2014
DOI: 10.1021/bm501516r
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Poly(2-aminoethylmethacrylate) and Poly(N-(2-aminoethylmethacrylamide) Modified Cellulose Nanocrystals: Synthesis, Characterization, and Cytotoxicity

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…Cellulose nanocrystals (CNCs) have gained increasing attention for cationic modification in the material community. Their unique chemical and mechanical properties, especially large surface area with high accessibility enable high density of substituents, and a variety of functional groups, including pyridinium (Jasmani, Eyley, Wallbridge, & Thielemans, 2013), quaternary amine (Zhu et al, 2014;Rosilo et al, 2014;Zaman, Liu, Xiao, Chibante, & Ni, 2013;Salajková, Berglund, & Zhou, 2012), poly(2-aminoethylmethacrylate), poly[N-(2-aminoethylmethacrylamide)] (Hemraz et al, 2015), poly[2-(dimethylamino)ethyl methacrylate] (Tang et al, 2014), polyamidoamine dendrimer (Tehrani & Basiryan, 2015) and poly(4-vinylpyridine) (Kan, Li, Wijesekera, & Cranston, 2013) have been successfully covalently bonded to CNCs. And the cationic CNCs could found a wide range of applications, such as sorbent (Zhu et al, 2014), biodegradable flocculants (Kan et al, 2013) surface finishing agent (Zaman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanocrystals (CNCs) have gained increasing attention for cationic modification in the material community. Their unique chemical and mechanical properties, especially large surface area with high accessibility enable high density of substituents, and a variety of functional groups, including pyridinium (Jasmani, Eyley, Wallbridge, & Thielemans, 2013), quaternary amine (Zhu et al, 2014;Rosilo et al, 2014;Zaman, Liu, Xiao, Chibante, & Ni, 2013;Salajková, Berglund, & Zhou, 2012), poly(2-aminoethylmethacrylate), poly[N-(2-aminoethylmethacrylamide)] (Hemraz et al, 2015), poly[2-(dimethylamino)ethyl methacrylate] (Tang et al, 2014), polyamidoamine dendrimer (Tehrani & Basiryan, 2015) and poly(4-vinylpyridine) (Kan, Li, Wijesekera, & Cranston, 2013) have been successfully covalently bonded to CNCs. And the cationic CNCs could found a wide range of applications, such as sorbent (Zhu et al, 2014), biodegradable flocculants (Kan et al, 2013) surface finishing agent (Zaman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is crucial to make sure no damage to the original morphology of the nanocrystals occurs during the surface functionalization process and as such, mild chemical methods are required to maintain the integrity of the nanocrystals. A number of surface covalent functionalizations of CNCs has been reported and some common examples include oxidation (tetramethylpiperidinyloxyl radical (TEMPO) oxidation for conversion of the primary hydroxyl groups to carboxylic acids [32] and periodate oxidation of vicinal diols to afford dialdehyde functionalities [33]), esterification [34,35], amidation [36,37], carbamation [38,39], amine functionalized CNCs (conversion of hydroxyl group to a terminated primary amine group) [40,41], radical polymerization [42][43][44][45], etherification, and other chemical modifications [2,29]. Readers are directed to a more detailed and critical review by Eyley and Thielemans on surface modifications of CNCs [29].…”
Section: Surface Covalent Functionalization Of Cncsmentioning
confidence: 99%
“…The main LRP techniques include atom transfer radical polymerization (ATRP), reversible addition fragmentation chain transfer (RAFT), and nitroxide-mediated polymerization (NMP), which have been exploited for the modification of polysaccharides towards the formation of high-performance hybrids [66,67]. These LRP techniques have also been employed on the surface of colloidal CNCs for the grafting of several functional polymer brushes with tunable or stimuli-responsive properties [42][43][44][45][68][69][70][71]. Surface-initiated atom transfer radical polymerization (SI-ATRP) and single-electron transfer living radical polymerization (SI-SET-LRP) are the most widely used methods for grafting from of polymers on the surface of CNCs.…”
Section: Cationic Cncs Via Polymerization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the wide potential therapeutic applications of CNCs in addition to their needle-like morphological features, a thorough understanding of the interaction of CNCs with the biological system is crucial for investigating any possible associated health risks. From a toxicological point of view, several studies have shown that pristine CNCs, fluorescently labeled CNCs, and surface-modified CNCs exhibited low cytotoxicity under the conditions tested with various cell lines or aquatic species [16][17][18][19][20][21][22]. While cytotoxicity assessment is the first crucial step in determining the suitability of a material for biomedical applications, further detailed investigation of any potential immunological response is also recommended [12].…”
Section: Introductionmentioning
confidence: 99%